Chemical constituents of thermal stress induced Ganoderma applantum (Per.) secondary metabolites on larvae of Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus and histopathological effects in mosquito larvae. (July 2019) - Logeswaran, C.; Vivekanandhan, P.; Shivakumar, M.S.
Abstract: Entomopathogenic fungus contains variety of secondary metabolites, which are known to have pharmacological and insecticidal properties. Stress plays an important role in production of toxic secondary metabolites. Thermal stress plays major role in production of toxic compounds. In the present study the toxicity of thermal temperatures induced G. applantum secondary metabolites were tested for larvicidal activities on Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus. Our results show that after 24 h post treatment, stress induced G. applantum ethyl acetate extract produce strong larvicidal activity in An. stephensi (LC50 : 53.035 mg/l), Cx. quinquefasciatus (LC50 : 85.618 mg/l), and Ae. aegypti (LC50 : 90.018 mg/l). G. applantum secondary metabolites were characterized using TLC and FT-IR. FT-IR shows two major functional groups which are, OH stretch and carboxylic groups. GC-MS analysis shows presence of two major compounds namely, Benzyl Chloroformates and hexyl nitro cyclohexene. Histopathological study shows that G.applantum extract, produce vacuolation in epithelial cells of midgut, far body and muscle tissues in mosquito larvae. Our overall findings suggest that thermal stress induced G. applantum culture, can produce virulent metabolites are toxic to mosquito larvae. These secondary metabolites can be used for effective, green pesticides for future mosquito control programs.